Rifampicin decreases neuroinflammation to maintain mitochondrial function and calcium homeostasis in rotenone-treated zebrafish - ALTURFAN, EBRU IŞIK (TAYLOR & FRANCIS LTD, 2022)
Among the mechanisms underlying Parkinson's disease, many pathogenic mechanisms are suggested to be effective such as oxidative stress, mitochondrial dysfunction, disruption of the ubiquitin-proteasome system, and neuroinflammation. Calcium is very important for neuronal and glial cells, neurodegenerative disease mechanisms are closely related to disturbed calcium homeostasis. Recent studies strongly support the role of inflammation in nigrostriatal degeneration in PD. In recent years, Rifampicin, a macrocyclic antibiotic has been shown to have a protective effect on neurons. This study aims to evaluate the effects of rifampicin in the experimental PD model induced by rotenone in zebrafish focusing on the relationship between calcium-dependent mitochondrial dysfunction and inflammation. Adult zebrafish were exposed to rotenone and rifampicin for 3 weeks. Locomotor activity was determined as the total distance that the zebrafish traveled for 5 min. Neuroinflammation and PD-related gene expressions were determined by RT-PCR. Mitochondrial calcium levels were determined using inductively coupled plasma-optical emission spectrometry (ICP-OES). Gamma synuclein, Park 7, Sigma-1 receptor expressions were determined by Western Blot. Our results show that rifampicin may be effective in reducing neuroinflammation, which may be an effective strategy to reduce mitochondrial dysfunction due to impaired calcium homeostasis in PD.
Keywords: Rifampicin; Parkinson’ s disease; neuroinflammation; calcium; zebrafish